The Correlation between Visual, Auditory, and Kinesthetic Learning Styles with SOOCA Examination Scores in Students of the Faculty of Medicine, Hang Tuah University, Surabaya - Vijaya, Ailya Tefanya; Wibowo, Prajogo; Mutiadesi, Wahyu Prasasti; Handajani, Fitri (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2023)
Learning style is one way that someone chooses to understand the material more quickly and easily. Everyone needs to identify their learning style in order to determine the most efficient learning method according to their characteristics. There are three kinds of learning styles, namely visual, auditory, and kinesthetic learning styles. Every student has a basis for this learning style, but not all of them develop proportionally, but some become dominant. This research was conducted to determine the relationship between the three learning styles and sooca exam scores in students of the Faculty of Medicine, Hang Tuah University, Surabaya. This research uses quantitative methods. The population in this study were all pre-clinical students in semesters 2, 4, 6 with active student status at the Faculty of Medicine, Hang Tuah University, Surabaya who took the SOOCA (structure Objective Oral Examination) exam and were willing to fill out the questionnaire in the period of June to December 2022. The sample size was obtained in the time period is 86 respondents. The results showed that out of 86 respondents, 3 (3.5%) were 18 year old students, 10 (11.6%) were 19 year old students, 26 (30.2%) were 20 year old students, 39 (45.4%) ) students aged 21 years, 8 (9.3%) students aged 22 years. A total of 64 (74.4%) respondents were female, and 22 (25.6%) respondents were male. 13 (15.1%) respondents have a visual learning style, 13 (15.1%) respondents have an auditory learning style, and 60 (69.8%) respondents have a kinesthetic learning style. Conclusion of this study is that there is no relationship between Visual, Auditorial, and Kinesthetic Learning Styles with Sooca Examination Scores in students of the Faculty of Medicine, Hang Tuah University, Surabaya. The learning styles of the students of the Faculty of Medicine, Hang Tuah University, Surabaya, class of 2018, 2019 and 2020, mostly have a kinesthetic learning style.